Upaya Deteksi Dini Penularan Tuberkulosis Pada Anggota Keluarga Kontak Serumah Penderita TB Aktif Menggunakan Uji Tuberkulin - Rafika Rafika; Nurlia Naim; Ridho Pratama; Dhia Istiqomah (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
Screening tests of tuberculosis transmission on family members living in housemates are attempts to increase the discovery of tuberculosis cases and are important in the control of tuberculosis. Positive TB event figures at the community Hall of Public Lung Health (BBKPM) in Makassar the defense is experiencing a tendency to increase so that the risk of transmission will increase especially against family members because of the transmission of TB through droplet infection. The activities of this Community devotion to improving the capacity of health workers in the efforts of the prevention of tuberculosis disease by enhancing the early detection ability of tuberculosis disease transmission in family members of housemates. The method of this dedication by conducting the Tuberculin test in the family contact of patients with active TB in BBKPMM. This activity is conducted from July to October 2019. Diagnosis of examination is conducted by nurses and medical laboratory energy analysts. The family member of the patient who is used as a participant in this activity is a family of active TB sufferers in the treatment room of the second floor in BBKPMM. Results of the test tests of tuberculosis from 45 members of the household contacts of patients with active Lung Tuberculosis obtained 22 people (49%) Positive and 23 people (51%). The results of this activity as an input for the BBPKMM will do follow up for the positive family members of the sufferer.